2019
DOI: 10.12693/aphyspola.136.713
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of the Preisach Model for Grain Oriented Steel

Abstract: The full material characteristics in the Preisach model of hysteresis is a two-dimensional weighting function. It can be determined experimentally from systematic measurement of partial hysteresis loops followed by derivation of their decreasing parts. Because of measurement errors, the derivation is not correct. Nevertheless, basic material features can be obtained either from incomplete measurement that uses the Preisach triangle respecting the measurement errors. The non-uniform grid in the Preisach model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Eichler et al suggested that the use of a nonuniform grid applied to hysteron distribution might improve the overall performance of the Preisach model and its accuracy for hysteresis loops in GO steel [55]. The proposed approach allowed them to increase the computation speed by two orders of magnitude; however, it required more complicated pre-processing grid data necessary for modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Eichler et al suggested that the use of a nonuniform grid applied to hysteron distribution might improve the overall performance of the Preisach model and its accuracy for hysteresis loops in GO steel [55]. The proposed approach allowed them to increase the computation speed by two orders of magnitude; however, it required more complicated pre-processing grid data necessary for modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The most common approaches are the Gaussian normal distribution [ 65 , 132 , 160 , 174 ] and the Lorentzian (or Cauchy–Lorenzian) distribution [ 164 , 175 , 176 ], but some also use the log-normal distributions [ 141 , 177 ]. The Lorentzian distribution is based on the arctan function [ 173 , 178 , 179 , 180 ], which has a similar sigmoid shape that includes saturation.…”
Section: Preisach Modelmentioning
confidence: 99%
“…Measurements of first-order reversal curves are the most common way to identify the Preisach distribution as seen in several studies [ 180 , 191 , 197 , 198 , 199 , 200 ]. However, this method could have limited applicability when affected by noise [ 201 ].…”
Section: History By Reversal Curvesmentioning
confidence: 99%
“…One approach is based on the arctan-function [173], and could be considered an approximation of the Langevin function [49]. The arctan function could be related to a statistical approach by Cauchy-Lorenzian distribution [325][326][327][328][329][330][331]. There are many statistical functions that are sigmoid shaped.…”
Section: Statistical Distributionsmentioning
confidence: 99%